SISTEM PEMBAYARAN TAGIHAN RUMAH SAKIT MENGGUNAKAN METODE HOST TO HOST PADA RSUD BUNG KARNO KOTA SURAKARTA - Nuryadi; Widatama, Krisna (Jurnal Informatika, Komputer dan Bisnis (JIKOBIS), 2022)
The payment system plays an important role in the process of transactions carried out by institutions, agencies, companies and individuals. Problems arise in the use of the payment system at the Bung Karno Hospital which causes hospital services to be inefficient. Problems that arise in the payment system have an impact on patient care and hospital management at the Bung Karno Hospital. The Host to Host payment system is a solution to payment problems at the Bung Karno Hospital. This study uses the Host To Host method with an online basis that is integrated with Bank Jateng. The implementation of the Host To Host system with Bank Jateng makes the patient payment process have an alternative payment method where the patient can pay bills with the features of Bank Jateng. The implementation of the Host To Host System with Bank Jateng at the Bung Karno Hospital makes patient service more efficient. This system also helps the hospital in managing financial management.